PENGARUH ORIENTASI BELANJA DAN PERBEDAAN GENDER TERHADAP PENCARIAN INFORMASI ONLINE DAN BELANJA ONLINE PADA MAHASISWA JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI MALANG - Dwi Sudjanarti; Umi Khabibah; Tri Istining Wardani (Adbis: Jurnal Administrasi dan Bisnis, 2018)
This study aims to determine the effect of shopping orientation on online information search and online shopping, as well as differences in men and women in shopping orientation. The type of research used in this study is quantitative research with descriptive causal types. The study population was students of the 2017/2018 Academic Year of Malang State Polytechnic who had made an online purchase. Data collection uses a questionnaire to 94 respondents using purposive random sampling technique. Data analysis uses simple regression. The results showed that shopping orientation did not affect the online information search with t count 0.547 t table 1.66159. The simple regression equation obtained is Y1 = 7.898 + 0.013 X and Y2 = 2.492 + 0.082 X. The results of the study show that there is no difference in shopping orientation between men and women.